Direito de laje como forma de empreender - Santos, Regina Bonilha dos (2024)
Land title regularization has always been a concern throughout the social evolution and history of Brazil. The right to a decent housing for the low-income population in communities and the regularization of these properties built on elevated structures became the subject matter of legislative innovation on December 22, 2016, with the issuance of Provisional Measure No. 759 converted into Law No. 13.465 of July 11, 2017. Despite its broad thematic scope, this law provides for rural and urban land title regularization, the settlement of credits granted to agrarian reform settlers and land title regularization within the scope of Legal Amazon. The law also establishes mechanisms to enhance the efficiency of procedures for the disposal of Union properties and amends several laws, especially the one relevant for this research, Law No. 10.406, dated January 10, 2022, which introduced a new type of title in Article 1.225, XIII of the Civil Code, known as the Direito Real de Laje, “Slab Real Law”, and consequently a new title, Title XI, was added to Book III, Property Law, which addresses the new legal concept specifically in Articles 1.510-A to 1.510-E. The purpose of this study is to analyze this new title in details, which has a great relevance in the Brazilian legal-social scenario, particularly in housing issues, considering its inclusion in the Civil Code as a whole, tracing its historical origin and technical basis. Moreover, the study explores the challenges of its application in the context that led to its creation and demonstrates the potential for its use in economic exploration within the real estate market. Lastly, the research aims to analyze the foreign legislation, classify and differentiate it from similar institutes and make final considerations that may serve as a construction guide within Brazilian Civil Law